SARS-CoV-2 infection, antibody positivity and seroconversion rates in staff and students following full reopening of secondary schools in England: A prospective cohort study, September–December 2020. (July 2021) - Ladhani, Shamez N.; Ireland, Georgina; Baawuah, Frances; Beckmann, Joanne; Okike, Ifeanyichukwu O.; Ahmad, Shazaad; Garstang, Joanna; Brent, Andrew J.; Brent, Bernadette; Walker, Jemma; Aiano, Felicity; Amin-Chowdhury, Zahin; et al.
Abstract: Background: Older children have higher SARS-CoV-2 infection rates than younger children. We investigated SARS-CoV-2 infection, seroprevalence and seroconversion rates in staff and students following the full reopening of all secondary schools in England. Methods: Public Health England (PHE) invited secondary schools in six regions (East and West London, Hertfordshire, Derbyshire, Manchester and Birmingham) to participate in SARS-CoV-2 surveillance during the 2020/21 academic year. Participants had nasal swabs for RT-PCR and blood samples for SARS-CoV-2 antibodies at the beginning (September 2020) and end (December 2020) of the autumn term. Multivariable logistic regression was used to assess independent risk factors for seropositivity and seroconversion. Findings: Eighteen schools in six regions enrolled 2, 209 participants, including 1, 189 (53.8%) students and 1, 020 (46.2%) staff. SARS-CoV-2 infection rates were not significantly different between students and staff in round one (5/948; [0.53% ] vs. 2/876 [0.23%] ; p  = 0.46) or round two (10/948 [1.05%] vs. 7/886 [0.79%] ; p  = 0.63), and similar to national prevalence. None of four and 7/15 (47%) sequenced strains in rounds 1 and 2 were the highly transmissible SARS-CoV-2 B.1.1.7 variant. In round 1, antibody seropositivity was higher in students than staff (114/893 [12.8%] vs. 79/861 [9.2%]; p  = 0.016), but similar in round 2 (117/893 [13.1%] vs.117/872 [13.3%]; p  = 0.85), comparable to local community seroprevalence. Between the two rounds, 8.7% (57/652) staff and 6.6% (36/549) students seroconverted ( p  = 0.16). Interpretation: In secondary schools, SARS-CoV-2 infection, seropositivity and seroconversion rates were similar in staff and students, and comparable to local community rates. Ongoing surveillance will be important for monitoring the impact of new variants in educational settings.